Towards Environmental Innovation Systems - Weber, K. Matthias; Hemmelskamp, Jens.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
The book brings together research communities from different disciplines and countries, and offers an exchange about theoretical frameworks and practical experiences to guide research and policy "towards environmental innovation systems". The contributions selected explore new directions of research at the borderline between two established research traditions: systems of innovation and environmental innovations. For this purpose, the book draws on recent conceptual and empirical insights as well as on policy-oriented analyses. It is structured according to the four main areas of interest with respect to environmental innovation systems: conceptual foundations, empirical experiences, strategic approaches, and experiences with policy instruments.
Co-Evolution of Technical, Environmental and Social Systems -- On the Co-Evolution of Technologies and Institutions -- The Management of the Co-Evolution of Technical, Environmental and Social Systems -- Technological Regimes, Environmental Performance and Innovation Systems: Tracing the Links -- Merging Research Perspectives on Innovation Systems and Environmental Innovation: An Introduction -- National, Regional and Sectoral Innovation Systems and Sustainable Development -- Can Poland's Success in Environmental Policy Reforms Translate into Technological Innovation for Environment? -- Sustainable Development and the Regional Dimension of the Innovation System -- Green Innovation in Nordic Energy Industry: Systemic Contexts and Dynamic Trajectories -- Public Policy, Voluntary Initiatives and Water Benign Process Innovations: Empirical Evidence from the West German Chemical Industry during the Mid-1990s -- Strategies for Environment and Innovation -- Government and Environmental Innovation in Europe and North America -- Ecological Modernisation and the Creation of Lead Markets -- Innovation, Time and Sustainability -- Integrated Long-Term Strategies to Induce Regime Shifts towards Sustainability: The Approach of Strategic Niche Management -- Policies and Conditions for Environmental Innovation and Management in Industry -- Policy Assessment (Issues) and New Requirements -- The Need for Environmental Innovation Indicators and Data from a Policy Perspective -- Innovations in the Environmental Policy System: Voluntary, Collaborative and Information-Based Policies in the United States and the Netherlands -- The IPPC Directive and Factors Influencing the Economic and Environmental Performance of Firms and Plants in the Cement, Non-Ferrous Metals and Pulp and Paper Sectors in the EU -- Back-Casting for Environmental Sustainability: From STD and SusHouse towards Implementation -- Towards Environmental Innovation — A Policy Synthesis.
Keywords: Environmental economics; Economic policy; Environmental Economics; R & D/Technology Policy